2004
DOI: 10.1042/bst0320075
|View full text |Cite
|
Sign up to set email alerts
|

Enterocyte fatty acid uptake and intestinal fatty acid-binding protein

Abstract: This article reviews our current understanding of the uptake of fatty acids by the enterocytes of the intestine. The micellar solubilization of fatty acids by bile salts and the factors regulating that process are discussed. The mechanism of how micellar solubilization of fatty acids promotes the uptake of fatty acids by enterocytes and their relative importance is reviewed. Additionally, discussion of the various fatty acid transporters located at the brush border membrane of the enterocytes is included. Fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 25 publications
1
23
0
2
Order By: Relevance
“…FATP4 was found to be up-regulated 2.2-fold after weaning, whereas CD36 was downregulated 1.8-fold, raising the possibility of different functional importance of the two transporters during the intestinal development. The upregulation of FATP4 supports the argument of Tso et al (34) that with a low concentration of fatty acids, they are taken up actively with transporters, whereas with a high concentration, the majority are taken up passively by the enterocytes.…”
Section: Establishment Of Label-free Quantitative Proteomics Of In-supporting
confidence: 73%
See 1 more Smart Citation
“…FATP4 was found to be up-regulated 2.2-fold after weaning, whereas CD36 was downregulated 1.8-fold, raising the possibility of different functional importance of the two transporters during the intestinal development. The upregulation of FATP4 supports the argument of Tso et al (34) that with a low concentration of fatty acids, they are taken up actively with transporters, whereas with a high concentration, the majority are taken up passively by the enterocytes.…”
Section: Establishment Of Label-free Quantitative Proteomics Of In-supporting
confidence: 73%
“…There is some controversy whether fatty acids are taken up passively by diffusion or actively via specific transporters located in the apical plasma membrane of enterocytes (34). We identified two transporters presumed to be involved in intestinal fatty acid uptake: FATP4, which has been suggested to play a key role in the uptake of long-chain fatty acids and to be the principal fatty acid transporter in enterocytes (35); and platelet glycoprotein (CD36) ( Table I).…”
Section: Establishment Of Label-free Quantitative Proteomics Of In-mentioning
confidence: 98%
“…The first step in lipid absorption, the movement of monoacylglycerols and fatty acids across the apical membrane of enterocytes, is not well defined on a molecular level; it very likely involves different mechanisms. Several studies describe protein-dependent mechanisms, although others have reported protein-independent transport via diffusion through the apical membrane of the enterocytes (39,40) for which in particular bile salts appear to be necessary as they form micelles with the fatty acids and facilitate thereby their absorption (41). Lipids also might be taken up via endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that BOO, in a relatively small amount, can significantly suppress dietary fat absorption in humans. Micellar solubilization of hydrolysis products of triacylglycerols is one of the important processes of fatty acid absorption in the intestine 7,8 . In addition to the inhibition of pancreatic lipase activity by BOO, our results in which BOO increased the excretion of all the dietary fatty acids also suggest that BOO and its hydrolysis products might suppress micellar solubility of hydrolysis products of triacylglycerols, such as free fatty acids and monoacylglycerols, other than BOO.…”
Section: Discussionmentioning
confidence: 99%